Bioelectricity generation from sago hampas by Clostridium beijerinckii SR1 using microbial fuel cells - Jenol, Mohd Azwan (2020)
Sago hampas is a starch-based biomass resulted from the sago starch extraction process that has potential to be a substrate for bioenergy production. Microbial fuel cells (MFCs) is a promising technology that employ the microorganisms to utilize the substrate, which then generate the electrical power. Therefore, through the concept of biomass fuel cells, this study was aimed to utilize sago hampas as substrate in microbial fuel cells to generate the bioelectricity by Clostridium beijerinckii SR1, via sugar and volatile fatty acids (VFAs) platform and direct biomass utilization system. A single culture, C. beijerinckii SR1 has been employed to produce VFAs from 40 g/L of sago hampas (containing 20 g/L of starch content), resulted 6.71 g/L of total VFAs with the VFAs yield of 0.30 g/g. The enhancement of VFAs from sago hampas was conducted using one-factor-at-a-time (OFAT) with the variables of carbon sources concentration, nitrogen (yeast extract) concentration and addition of inorganic nitrogen sources. The production of VFA has successfully enhanced by 14.6%, with the OFAT condition obtained was 3% (w/v) of sago hampas, 3 g/L of yeast extract and the additional 2 g/L of NH4NO3, resulted the production of VFAs (7.69 g/L) with 0.45 g/g of VFAs yield. Furthermore, the effect of sugar and VFAs platform from sago hampas on the bioelectricity generation using microbial fuel cells were studied. The results showed the VFAs platform of sago hampas has better bioelectricity generation, in term of maximum power density (max PD) as compared to sugar platform. The highest max PD obtained was 72.62 mW/m2 from 2 g/L of VFAs hydrolysate. At the final stage, direct biomass fuel cells was performed using sago hampas directly as a substrate in MFCs. Result shown that 73.78 mW/m2 of maximum power density was obtained from direct biomass fuel cells by C. beijerinckii SR1. This result shows a comparable maximum power density as compared to VFAs platform of sago hampas. Overall, the generation of bioelectricity from sago hampas has been successfully studied using microbial fuel cells system by C. beijerinckii SR1.